Renoprotective effect of crocin following liver ischemia/ reperfusion injury in Wistar rats - Seyyed Ali Mard; Ghaidafeh Akbari; Esrafil Mansouri; Mahdi Parsanahad (Iranian Journal of Basic Medical Sciences, 2017)
Objective(s): The objectives of the current study were to evaluate the effects of hepatic ‎ischemia/reperfusion (IR) injury on the activity of antioxidant enzymes, biochemical factors, and ‎histopathological changes in rat kidney, and to investigate the effect of crocin on IR-‎related changes. Materials and Methods: Thirty-two male Wistar rats were randomly allocated into four groups (n=8). They were ‎sham-operated, IR, crocin pre-treatment, and crocin pretreatment+IR groups. Sham-operated ‎and Crocin pre-treatment groups received normal saline (N/S, 2 ml/day) and crocin (200 mg/kg) ‎for seven consecutive days intraperitoneally (IP), respectively, then rats underwent laparotomy, only. ‎IR and crocin pretreatment+IR groups received N/S and crocin with the same dose, time, and route, ‎respectively, then rats underwent partial (70%) ischemia for 45 min that was followed by reperfusion ‎for 60 min. At the end of the experiment, kidney specimens were taken for histopathological and ‎antioxidant evaluations and also blood samples were obtained for biochemical analysis. Results: The results of the present study showed that crocin pre-treatment significantly increased ‎the activity of antioxidants, decreased the serum levels of liver enzymes and blood urea nitrogen ‎following IR-induced hepatic injury. Crocin also ameliorated kidney´s histopathological ‎disturbance beyond IR-induced hepatic injury. Conclusion: Crocin as an antioxidant agent protected renal insult following liver IR injury by ‎increasing the activity of antioxidant enzymes, reducing serum levels of liver enzymes, and ‎improving histopathological changes.‎